Solid-State Drawing of Commercial Poly(Lactic Acid) (PLA) Based Filaments - Walker, Julian; Melaj, Mariana; Giménez, Rocio; Pérez, Ezequiel; Bernal, Celina (Frontiers in Materials, 2019)
In the present work, solid-state drawing of commercial PLA-based extruded filaments was investigated. Two different filaments were used: one based on neat PLA and the other based on PLA filled with copper particles. The effect of the processing parameters such as the drawing temperature and the draw ratio on the material morphology and thermal and mechanical behavior was analyzed. A specially designed device which simulates the solid-stated drawing stage frequently used for fibers manufacturing was applied. The drawing effects were evidenced by the results of the degree of crystallinity and tensile parameters, as well as by SEM analysis and topographical observations of the surfaces of the filaments. From these results, it was concluded that the draw ratio is more important than the drawing temperature as a determining factor of the tensile performance of the PLA-based filaments investigated. However, the drawing temperature plays a key role to establish the critical draw ratio to obtain stable solid-state drawing.